Réponse de quatre variétés de Anacardium occidentale L. aux techniques de greffage horticole en pépinière - Touré Mamoudou Abdoul; Faye Elhadji; Goudiaby Ramatoulaye (VertigO)
The nuts Production of Anacadium occidental L. in Senegal is low and the quality is also poor compared to its competitors (Bissau Guinea, Ivory Coast, etc.). This situation is due to some factors including use lack of selected and improved varieties, aging plantations, and lack of farmers’ training. Few studies have been conducted on the grafting using different morphotypes and grafting techniques for this species. The objective of the study was to help improve the effective multiplication of A. occidental L. best varieties. To do so, a grafting test of juvenile and adult material using four (4) rootstocks corresponding to the "varieties" of western A. occidentale L. Costa Rica, Henry, James and Yellow Benin and two grafting techniques (terminal slit and simple English) was realized. The results obtained show that juvenile grafts survival rate reached 95.83 % whatever the grafting technique was. The survival rate was also a function of the grafting technique (p